Islam Berkemajuan: A Synthesis of Islamic Values and Civilizational Progress - Athar Abdullatif Husain; Bagus Jamroji; Roni Nuryusmansyah; Addinul Subhan (PT. Education Research Center, 2026)
Islam Berkemajuan is a distinctive paradigm developed by Muhammadiyah, referring to progressive and civilizational Islam that integrates Islamic normative values with modern societal demands. This study analyzes Islam Berkemajuan within the Al-Islam and Kemuhammadiyahan perspective, examining how Islamic values synthesize with civilizational progress in Muhammadiyah thought. Employing a qualitative library research approach, this study examines authoritative sources including Al-Islam and Kemuhammadiyahan literature, official Risalah Islam Berkemajuan, Muhammadiyah congress documents, and relevant scholarly works. Data were analyzed using descriptive-analytical techniques to identify key concepts and theoretical linkages. Findings reveal that Islam Berkemajuan represents an integrative paradigm uniting theological principles tauhid, justice, and humanity with rationality, scientific development, and social transformation. This synthesis operates through tajdid, functioning as both doctrinal purification and continuous renewal across social, educational, and cultural domains. The study's novelty lies in positioning Islam Berkemajuan explicitly as civilizational synthesis within Al-Islam and Kemuhammadiyahan framework, transcending mere normative rhetoric. The conclusion establishes Islam Berkemajuan as a relevant, dynamic framework for understanding Islam as both ethical guidance and civilizational progress, contributing significantly to Al-Islam and Kemuhammadiyahan studies development.